KEGUNAAN KEPUTUSAN INFORMASI AKUNTANSI (DECISION USEFULNESS) DARI PERSPEKTIF INVESTOR BURSA EFEK INDONESIA: SEBUAH STUDI FENOMENOLOGI - Made Sudarma; Putu Wulandari (KRISNA: Kumpulan Riset Akuntansi, 2025)
The decision usefulness of accounting information becomes important when financial statements and the information in them are used as a basis for decision making by investors in the capital market. Providing useful and high-quality information about economic units is the main objective of financial reporting. The quality of financial statements is described as decision usefulness for users of accounting information in financial statements. There is a gap between what is regulated by regulators in defining accounting information that is useful to stakeholders and the reality of how investors make investment decisions based on information in financial statements. It is important to investigate whether accounting information in financial statements is still used as the basis for investor decision making by understanding the decision usefulness of accounting information from the investor's perspective. The transcendental phenomenological approach and interpretive paradigm are used in this study to deeply understand how investors interpret the usefulness of accounting information decisions in decision making through experience as the most basic awareness. The results showed that investors interpret the usefulness of accounting information decisions based on the accuracy of representation where accounting information will be useful if the financial statements are prepared in an integrated manner and are strongly influenced by the type of investor. While the usefulness of accounting information from qualitative characteristics is relevant, investors interpret it as useful information if there is information leakage and the existence of accounting manipulation or distortion.